Marketing Healthcare - Moschis G.P. (2023)
This chapter highlights several trends in the healthcare industry that provide opportunities for service providers of healthcare-related services to profit while enhancing the well-being of older adults. As older people realize the benefits of preventive healthcare for longevity and quality of life, they increasingly with age engage in activities, such as exercising and better nutrition, that help deter aging and the onset of chronic conditions. In response to this trend, healthcare service providers expand the scope of their services, making them available in a larger number of locations with the assistance of new technologies, such as adult day-care centers and the aging person’s private home. In addition, hospitals are attempting to reposition and expand their services from the traditional forms of acute care that are provided in the hospital to acute and long-term care that can be provided in various convenient and less costly locations. And they attempt to compete with other providers who can provide a variety of healthcare services in the community and the aging person’s home. Factors such as consumer preferences for receiving various healthcare services, rising healthcare costs, and emerging technologies are making the provision of healthcare services more profitable and desirable for the elderly when they are offered at locations most convenient to the aging person, contributing to the recipient’s well-being.